Le contrat racial - Mills, Charles W.; Webster (Mémoire d'encrier, 2023)
« Publié originalement en 1997 aux États-Unis, Le contrat racial du philosophe Charles W. Mills expose les failles du contrat social, qui est avant tout un contrat racial. Ce contrat a façonné le système de domination européenne qui fait exister les Blanc·he·s en tant que personnes à part entière et les non-Blanc·he·s en tant que sous-personnes. Charles W. Mills place la justice raciale au centre de ses analyses. Réfutant l’idée du contrat social, Mills évoque plutôt le contrat racial où l’ordre racial crée les assises de nos sociétés, la reconduction des privilèges et la domination. La présente édition a bénéficié d’une nouvelle préface de l’auteur, rédigée à l’occasion du 25e anniversaire de la parution du livre. »– Résumé de l'éditeur.
Section: 197 pages ; 23 cm. Donné en lecture cours POL4212: p.98-103; 132-140
Keywords: approches et analyses; contrat social; cours; discipline; histoire et politique; intersectionnalité; justice sociale; phi4336; pol4212; premier cycle; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques

Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »–Page 4 de la couverture.
Section: ix, 306 pages ; 24 cm.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques